The state of application of innovation approaches in physical education of regional education establishments - Масляк Ірина Павлівна, (Irina Maslyak); Мамешина Маргарита Анатоліївна, (Margarita Mameshina); Жук В’ячеслав Олександрович, (Vjacheslav Zhuk) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: to determine relation and degree of readiness of physical culture teachers of regional educational establishments for application innovation approaches in educational process. Material and Methods: in research 29 teachers of physical culture took part from town of Izum and Izum district of Kharkov region. The following methods were used: theoretical analysis and generalization of scientific literature, questioning, mathematic statistics. Results: it is established the positive relation of the physical culture teachers of regional schools innovation educational approaches: determined that only, approximately 50 percent teachers use their in education process. It is revealed that majority teachers strive for riding their educational experience, but doing that they feel deficit of scientific methodical literature directed to enhancing the level of their professional skill. Conclusions: it is determined the positive relation of teachers of physical culture of regional secondary schools to inculcate innovation technologies in educational training process, but they turned out prepared insufficiently for innovation activity.